MicroRNA-135a Protects Against Ethanol-Induced Apoptosis in Neural Crest Cells and Craniofacial Defects in Zebrafish by Modulating the Siah1/p38/p53 Pathway - Yuan, Fuqiang; Yun, Yang; Fan, Huadong; Li, Yihong; Lu, Lanhai; Liu, Jie; Feng, Wenke; Chen, Shao-yu (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs are small non-coding RNAs that are involved in various biological processes, including apoptosis, by regulating gene expression. This study was designed to test the hypothesis that ethanol-induced downregulation of miR-135a contributes to ethanol-induced apoptosis in neural crest cells (NCCs) by upregulating Siah1 and activating the p38 MAPK/p53 pathway. We found that treatment with ethanol resulted in a significant decrease in miR-135a expression in both NCCs and zebrafish embryos. Ethanol-induced downregulation of miR-135a resulted in the upregulation of Siah1 and the activation of the p38 MAPK/p53 pathway and increased apoptosis in NCCs and zebrafish embryos. Ethanol exposure also resulted in growth retardation and developmental defects that are characteristic of Fetal Alcohol Spectrum Disorders (FASD) in zebrafish. Overexpression of miRNA-135a significantly reduced ethanol-induced upregulation of Siah1 and the activation of the p38 MAPK/p53 pathway and decreased ethanol-induced apoptosis in NCCs and zebrafish embryos. In addition, ethanol-induced growth retardation and craniofacial defects in zebrafish larvae were dramatically diminished by the microinjection of miRNA-135a mimics. These results demonstrated that ethanol-induced downregulation of miR-135a contributes to ethanol-induced apoptosis in NCCs by upregulating Siah1 and activating the p38 MAPK/p53 pathway and that the overexpression of miRNA-135a can protect against ethanol-induced apoptosis in NCCs and craniofacial defects in a zebrafish model of FASD.